Evaluasi Pembelajaran Jarak Jauh-Belajar Dari Rumah (PJJ-BDR) Satu Tahun Masa Pandemik Covid-19 - Atrup, Atrup; Puspitarini, Ikke Yuliani Dhian (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
School closures and learning implemented through PJJ-BDR have been going on for more than a year. Some research has been done to test the effectiveness of PJJ-BDR. This research tries to compare the results of existing research with the information and data obtained in this research using a desk research approach. It can be concluded as follows; (1) learning from PJJ-BDR due to the covid-19 pandemic is the best choice regardless of the many obstacles faced by teachers, this is because it is still possible that the provision of learning services to students can still take place, (2) there are many things that determine the effectiveness of PJJ-BDR it is proven that some research show different results, and (3) PJJ-BDR learning for elementary school students is not effective. Suggestions that can be given are; (1) in order for the implementation of PJJ-BDR to be effective, it is recommended that teachers have high creativity and motivation for self-development and adapt to the application of learning applications, choosing the right learning strategy between online, offline and blended/hybrid learning, (2) to do PJJ - BDR well, it requires the attention of all parties in accordance with their respective roles of headmaster, heads of education offices, government and central government, and (3) it is recommended for further researchers to conduct research in accordance with the focus on the level and type of education.